A Discourse on Celebrity Influence on Consumers Patronage of Telecommunication Service Providers in Nigeria - Oghiagbepha, Oghenekevwe; Ijeh, Patrick Nkemdilim; Ufuophu-Biri, Emmanuel (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2024)
This study conceptually spotlighted the influence of celebrity endorsement on consumer’s patronage with major focus on telecommunication service providers in Nigeria. Using Globacom Nigeria Limited as a case study, it was acknowledged in the cause of the study that contemporary society is characterized with globalization and competition, because most consumers are exposed to alternative product. These propel business organizations to employ the most effective methods, strategies and programmes in producing and marketing their products and services. The study was rationalized by the reference group theory to link celebrity endorsement attributes and consumer purchasing behaviour as the exogenous and dependent variables of the study. Conclusion was drawn that celebrities have traditionally been the simplest way to debut a new product (consumer goods), and this will likely continue in the near future due to their broad popularity and a large following of devoted followers, mostly in the West. As a recommendation, the study suggested that marketing companies should ensure that their celebrity have a trustworthy nature, as this will influence the behavior of their consumers.